2019
DOI: 10.1371/journal.pntd.0007305
|View full text |Cite
|
Sign up to set email alerts
|

A community-based knowledge, attitude, and practice survey on rabies among cattle owners in selected areas of Bhutan

Abstract: Rabies remains a disease of significant zoonotic and economic concern in rabies endemic areas of Bhutan. Rabies outbreaks in livestock threaten the livelihoods of subsistence farming communities and pose a potential public health threat. As a part of identifying approaches to prevent rabies in cattle, a Knowledge, Attitude, and Practice (KAP) survey was conducted among cattle owners in selected rural areas of the southern rabies high-risk zone and low-risk zone in eastern Bhutan. Between March and April 2017, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 22 publications
8
46
0
6
Order By: Relevance
“…One of the critical findings of this survey is that the majority of the respondents revealed that they did not seek urgent medical care following a dog bite, consistent with similar studies on rabies in Pakistan [22]. However, this is in contrast to previously published studies on rabies in developed nations across the globe [11,13,18,23]. All these factors indicate that population in the study area are at a constant risk of disease because the participants lack sufficient knowledge regarding potential source, prevention, and control of rabies.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…One of the critical findings of this survey is that the majority of the respondents revealed that they did not seek urgent medical care following a dog bite, consistent with similar studies on rabies in Pakistan [22]. However, this is in contrast to previously published studies on rabies in developed nations across the globe [11,13,18,23]. All these factors indicate that population in the study area are at a constant risk of disease because the participants lack sufficient knowledge regarding potential source, prevention, and control of rabies.…”
Section: Discussionsupporting
confidence: 76%
“…A questionnaire covering three different sections and twenty three questions was prepared and used for data collection. Section 1 included six questions regarding the participants' demographic information, Section 2 nine contained questions related to respondents' knowledge, and Section 3 contained eight questions related with attitude and practices regarding rabies [13]. generated using open source Quantum GIS software specifically for the purpose of this study [13].…”
Section: Questionnaire Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…In Bhutan, dogs are the primary rabies reservoir, therefore two pathways (stray and pet dogs) were considered for this assesment. In the endemic areas of Bhutan, cattle are the most commonly affected livestock species (36,37). Due to the government's policy of achieving self-sufficiency in livestock produce, in addition to mobilization of cattle within the country, a large number of cattle have been imported from other countries posing risk of disease introduction and spread, inlcuding rabies.…”
Section: Discussionmentioning
confidence: 99%